2008
DOI: 10.1016/j.jana.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Coping With HIV-Related Stigma in Five African Countries

Abstract: People living with HIV (PLWH) and their families are subjected to prejudice, discrimination, and hostility related to the stigmatization of AIDS. This report examines how PLWH cope with HIV-related stigma in the five southern African countries of Lesotho, Malawi, South Africa, Swaziland, and Tanzania. A descriptive qualitative research design was used to explore the experience of HIV-related stigma of PLWH and nurses in 2004. A total of 43 focus groups were conducted with 251 participants (114 nurses, 111 PLWH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 11 publications
7
67
0
1
Order By: Relevance
“…Firstly, stigma as a trait is a characteristic that is viewed negatively by society, and secondly, stigma as an outcome occurs when the negative social meanings that are attached to the discrediting characteristic become labelled to an individual (Berger, Ferrans, & Lashley, 2001;Goffman, 1963). HIV-related stigmatisation is an example of this negative social labelling which alters the way people living with HIV are viewed and treated by others (enacted stigma), and how they view themselves (selfstigma) (Thorsen, Sundby, & Martinson, 2008 Several studies have shown that HIV-related perceived stigma may result in negative health behaviour such as non-adherence, avoiding HIV testing, non-disclosure of HIV status and poor patterns of accessing health care (Dlamini et al, 2009;Greeff & Phetlhu, 2007;Makoae et al, 2008;Mills, Nachega, Bangsberg et al, 2006;Mills, Nachega, Buchan et al, 2006;Nyblade & MacQuarrie, 2006;Peltzer, Mosala, Shisana, Nqueko, & Mngqundaniso, 2007;Plummer et al, 2006;Pulerwitz, Michaelis, Lippman, Chinaglia, & Diaz, 2008;Wolfe et al, 2006).…”
Section: Résumémentioning
confidence: 99%
“…Firstly, stigma as a trait is a characteristic that is viewed negatively by society, and secondly, stigma as an outcome occurs when the negative social meanings that are attached to the discrediting characteristic become labelled to an individual (Berger, Ferrans, & Lashley, 2001;Goffman, 1963). HIV-related stigmatisation is an example of this negative social labelling which alters the way people living with HIV are viewed and treated by others (enacted stigma), and how they view themselves (selfstigma) (Thorsen, Sundby, & Martinson, 2008 Several studies have shown that HIV-related perceived stigma may result in negative health behaviour such as non-adherence, avoiding HIV testing, non-disclosure of HIV status and poor patterns of accessing health care (Dlamini et al, 2009;Greeff & Phetlhu, 2007;Makoae et al, 2008;Mills, Nachega, Bangsberg et al, 2006;Mills, Nachega, Buchan et al, 2006;Nyblade & MacQuarrie, 2006;Peltzer, Mosala, Shisana, Nqueko, & Mngqundaniso, 2007;Plummer et al, 2006;Pulerwitz, Michaelis, Lippman, Chinaglia, & Diaz, 2008;Wolfe et al, 2006).…”
Section: Résumémentioning
confidence: 99%
“…As is true for studies in industrialised settings, existing studies from low-and middle-income countries predominately focus on the experience of HIV-related stigma, with less attention to people's resistance strategies (Dageid & Duckert, 2008;Makoae, Greeff, Phetlhu, et al, 2008;Poindexter, 2005;Rohleder & Gibson, 2006;Soskolne, 2003). In sub-Saharan Africa, studies of HIV-related stigma are predominately among populations where ARV treatment is not easily or freely available (Campbell, Foulis, Maimane & Sibiya, 2005;Kahn, 2004;Lindsey, Hirschfeld & Tlou, 2003;Olenja, 1999;Pool, Nyanzi & Whitworth, 2001;Rohleder & Gibson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to curb the HIV-related discrimination in order to promote the AIDS patients desire for, and receive antiviral treatment effectively. In most situations, because of the fear of being discriminated against, PLWHA will hide their infection status and continue to engage in high-risk behaviors, which exacerbate the spread of AIDS and leads to a worse quality of life (Makoae et al 2008;Bharat 2011). As far as we know, the study of the medical discrimination has mainly focused on the discrimination subjects, such as the public, medical staff, school teachers and so on (Memish et al 2015;Zarei et al 2015).…”
Section: Introductionmentioning
confidence: 99%